A Flexible and Pattern Reconfigurable Antenna with Small Dimensions and Simple Layout for Wireless Communication Systems Operating over 1.65–2.51 GHz - Ghaffar, A; Li, XJ; Awan, WA; Naqvi, AH; Hussain, N; Alibakhshikenari, M; Limiti, E (MDPI AG, 2021)
This research article proposes a compact frequency and pattern reconfigurable flexible antenna for heterogeneous applications. A triangular monopole antenna with a semicircular stub is made frequency and pattern tunable by connecting and disconnecting two inverted L-shaped stubs utilizing diodes. When either of the stubs is connected to the radiator, a relative phase difference happens at both ends of the radiator that changes the direction of the electromagnetic radiations, consequently pattern reconfigurability can be obtain. Besides that, because of the reactive load introduced by the stubs, the antenna’s effective length has changed and, as a result, the frequency reconfigurability can be attained. The antenna features a compact size of 40 × 50 × 0.254 mm3 corresponding to 0.22λo × 0.27λo × 0.001λo, where λo is free-space wavelength at 1.65 GHz, while its operational bandwidth is from 1.65 GHz to 2.51 GHz, with an average gain and radiation efficiency of better than 2.2 dBi and 80%, exhibiting a pattern reconfigurability of 180° in the E-plane. The frequency of the proposed antenna can be switched from 2.1 GHz to 1.8 GHz by switching the state of both diodes in OFF and ON-state, respectively. The fabricated prototype of the antenna is tested to verify its performance parameters. In addition, to validate the proposed design, it has been compared with prior arts in terms of the overall size, reconfigurability type, flexibility, radio frequency (RF) switch type used for reconfigurability, and frequency bandwidth. The proposed antenna provides smaller size with a large bandwidth coverage alongside with discrete RF switch type with the advantages of flexibility and both frequency and pattern reconfigurability. As a result, the proposed compact flexible and pattern reconfigurable antenna is a promising candidate for heterogeneous applications, including the global system for mobile (GSM) band (1800 and 1900 MHz) and industrial, scientific and medical (ISM) band (2.4 GHz) along with well-known cellular communication bands of 3G, 4G, and long term evolution (LTE) bands ranging from 1700–2300 MHz around the globe.
Keywords: Flexible antenna; Frequency reconfigurability; Pattern reconfigurable; 3G; 4G